2022
DOI: 10.1038/s41598-022-04788-w
|View full text |Cite
|
Sign up to set email alerts
|

Switchable deep eutectic solvent driven micellar extractive fermentation of ultrapure fibrin digesting enzyme from Bacillus subtilis

Abstract: Fibrinolytic protease (FLP) is a therapeutic enzyme used in the treatment of thrombolytic diseases. The present study proposed the concept of pH-driven swappable micellar two-phase extraction for the concurrent production and purification of FLP from Bacillus subtilis at cloud point extraction. Extractive fermentation was carried out with a pH swap mechanism and FLP was extracted to the top phase by surfactant deep eutectic solvents (SDES). Shrimp waste was chosen as a sustainable low-cost substrate that yield… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…2 (B). Also, NADES with high density was observed to exhibit low phase partitioning due to the densely packed top phase infiltrating water and target analyte to the bottom phase 37 , 38 . The phase formation mainly depends on various factors of NADESs including their moderate density and corresponding saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…2 (B). Also, NADES with high density was observed to exhibit low phase partitioning due to the densely packed top phase infiltrating water and target analyte to the bottom phase 37 , 38 . The phase formation mainly depends on various factors of NADESs including their moderate density and corresponding saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the high viscosity of DESs can be the strong interaction between the DESs components. Muniasamy et al determined the dependence of viscosity on temperature for all RDESs in the range 293 to 323 K [61]. It was found that the viscosity of all RDESs decreased nonlinearly with increasing temperature.…”
Section: Properties Of Rdessmentioning
confidence: 99%